2014
DOI: 10.1016/j.celrep.2014.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Blm-s , a BH3-Only Protein Enriched in Postmitotic Immature Neurons, Is Transcriptionally Upregulated by p53 during DNA Damage

Abstract: Programmed cell death is a pivotal process that regulates neuronal number during development. Key regulators of this process are members of the BCL-2 family. Using mRNA differential display, we identified a Bcl-2 family gene, Blm-s (Bcl-2-like molecule, short form), enriched in postmitotic neurons of the developing cerebral cortex. BLM-s functions as a BH3-only apoptosis sensitizer/derepressor and causes BAX-dependent mitochondria-mediated apoptosis by selectively binding to prosurvival BCL-2 or MCL-1. When ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…To investigate the function of BLM-s in vivo, we generated Blm-s -knockout ( Blm-s −/− ) mice. Because Blm-s transcript is an isoform of the Blm-l gene and is transcribed via the usage of alternative promoter and TSS located at the 24th intron of the Blm-l genome [ 31 ], we generated a Blm-s -specific knockout by removing the Blm-s genome but preserving the transcription of Blm-l gene (Fig. 1A and see Materials and Methods section).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the function of BLM-s in vivo, we generated Blm-s -knockout ( Blm-s −/− ) mice. Because Blm-s transcript is an isoform of the Blm-l gene and is transcribed via the usage of alternative promoter and TSS located at the 24th intron of the Blm-l genome [ 31 ], we generated a Blm-s -specific knockout by removing the Blm-s genome but preserving the transcription of Blm-l gene (Fig. 1A and see Materials and Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that BLM-s modulate the survival of immature postmitotic migratory neurons in the developing cortex under the stress of DNA double-strand breaks. RNAi-mediated knockdown of BLM-s in murine embryonic brains protects immature neurons from irradiation-induced apoptosis [ 31 ]. Accordingly, we assessed whether Blm-s −/− embryonic cortex is more resistant to apoptosis provoked by γ-irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrarily to this report, the present study revealed that MAPKs, including JNK, were constantly activated by TIPE1 overexpression in RAW264.7 cells. Erk, p38 and JNK could regulate mitochondrial functions, including the levels of Bcl-2 family proteins, to influence apoptosis progression (27)(28)(29)(30).…”
Section: C a Bmentioning
confidence: 99%